Volatile Compounds in Samples of Cork and also Produced by Selected Fungi - Barreto, M. C.; Boas, L. Vilas; Carneiro, L. C.; Rom, M. V. San; Vilas Boas, L.; San Romão, M. V. (Journal of Agricultural and Food Chemistry, 2011)
The production of volatile compounds by microbial communities of cork samples taken during the cork manufacturing process was investigated. The majority of volatiles were found in samples collected at two stages: resting after the ﬁrst boiling and nontreated cork disks. Volatile proﬁles produced by microbiota in both stages are similar. The releasable volatile compounds and 2,4,6-trichloroanisole (TCA) produced in cork-based culture medium by ﬁve isolated fungal species in pure and mixed cultures were also analyzed by gas chromatography coupled with mass spectrometry (GC-MS).The results showed that 1-octen-3-ol and esters of fatty acids (medium chain length C8C20) were the main volatile compounds produced by either pure fungal species or their mixture. Apparently,Penicillium glabrum is the main contributor to the overall volatile composition observed in the mixed culture. The production of releasable TCA on cork cannot be attributed to any of the assayed fungal isolates.
The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: 2; 2.4.6-trichloroanisole; 4; 6-trichloroanisole; Cork; fungi; volatile compounds